Norway : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper examines Kenya's growth performance during 1980-2004. It considers the stylized facts on Kenya's growth performance in the past two decades, in comparison with other Sub-Saharan African countries. The paper examines main sources of economic growth in Kenya, in the context of a conventional growth accounting exercise. It also considers the main determinants of the results indicated in the growth accounting exercise. The paper reveals that since the early 1990s, Kenya's economic performance has been weaker than the average for Sub-Saharan African countries.